2019
DOI: 10.1101/626879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The magnitude of neonatal mortality and its predictors in Ethiopia: a systematic review and meta-analysis

Abstract: AbstractsBackground: Although neonatal death is a global burden, it is the highest in Sub Saharan Africa countries such as Ethiopia. This study was aimed to provide pooled national prevalence and predictors of neonatal mortality in Ethiopia. Objective:To assess the pooled prevalence and predictors of neonatal mortality in Ethiopia.Search Strategy: global databases were systematically explored. Systematically searched using the following databases: Boolean operator, Cochrane library, PubMed, EMBASE, HINARI, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…Hypothermia and oxygen saturation < 90% during transportation was an independent predictor of neonatal death. This study is similar to a previous study conducted in Ethiopia [ 11 ], Mauritania [ 28 ], and India [ 2 , 12 ]. Lack of emergency care on the way to higher centers, poor stabilization before referral and inadequate care during transport increase clinical instability [ 2 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hypothermia and oxygen saturation < 90% during transportation was an independent predictor of neonatal death. This study is similar to a previous study conducted in Ethiopia [ 11 ], Mauritania [ 28 ], and India [ 2 , 12 ]. Lack of emergency care on the way to higher centers, poor stabilization before referral and inadequate care during transport increase clinical instability [ 2 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, neonatal mortality still continues increase from 29 to 30 deaths per 1000 live births between 2016 and 2019 and varies across regions. According to research finding neonatal mortality in the Amhara regional state is 20.3% [ 4 , 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study showed that neonates born to mothers residing in rural areas were at higher risk of neonatal mortality compared with those living in urban areas. This nding is in line with a meta-analysis nding in Ethiopia [10], a study in Nigeria [29] and another study from Gansu province China [55]. This can be related to the limited access to obstetric and neonatal care services such as low institutional delivery and caesarean delivery rates [56], limited sanitation and water supplies and a lower proportion of education and awareness about neonatal care in the rural areas [57].…”
Section: Discussionsupporting
confidence: 80%
“…Evidence from studies on neonatal survival in Ethiopia report inconsistent neonatal mortality rates. A meta-analysis that pooled prevalence studied showed an overall neonatal mortality rate of 163.5 per 1000 live births [10]. A nding from another systematic review and meta-analysis of 11 studies conducted after 2012 in Ethiopia reported a neonatal mortality rate of 67.8 per 1000 live births [11], but with considerable heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Like most Sub-Saharan countries, Ethiopia has a high neonatal mortality rate [10][11][12][13]. In 2012, Ethiopia had the sixth-highest neonatal mortality rate globally, with an estimated death of 87,800 neonates or 31 deaths per 1000 live births [14,15].…”
Section: Introductionmentioning
confidence: 99%